BIOMASS PRODUCTION AND CARBON SEQUESTRATION POTENTIAL OF SALIX ALBA PLANTATIONS UNDER TEMPERATE CONDITIONS OF KASHMIR (INDIA) - SHAH MURTAZA MUSHTAQ; TARIQ HUSSAIN MASOODI; PARVAIZ AHMAD KHAN; GOWHER NABI PARREY (International Journal of Pharma and Bio Sciences, 2014)
Quantifying carbon balance in plant biomass is necessary to determine the species specific greenhouse gas potential. This study is one of such attempts aimed to compare the C balances among various white willow (Salix alba) groves established across the four Districts (viz. Anantnag, Bandipora, Baramulla and Ganderbal of Kashmir valley. After conducting a detailed survey, two plantation blocks of white willow ranging in age from 1to 20years were selected in each of the four Districts. Five quadrates of 10 × 40 m (400 m2) size were laid at each plantation block for sampling of trees to record the various observations. The vegetation analysis of plantation groves revealed that Salix alba comprised the dominant position with distinctive density of 81.90 % and IVI of 213.80. The existing stem volume, biomass production, carbon density and carbon sequestration potential of trees at all the selected locations were evaluated employing standard methods. The maximum and minimum stem volume of 739.34 and 595.09 cum ha-1 and respective biomass production of 532.61and 429.27 t ha-1 was recorded at Bandipora and Anantnag. The maximum soil carbon density of 68.07t ha-1 was recorded at Bandipora, followed by 67.93 t ha-1 at Baramulla, 66.86t ha-1 at Ganderbal and 66.43t ha-1 at Anantnag. The results of this study further visualized that; on an average, white willow (Salix. alba) can store up to 292.98 tons of C ha-1 and Sequesters around 1075.24 CO2e tons ha-1 from the atmosphere. Thus enhancing carbon sequestration through commercial plantations of this species can prove to be a long term future policy option for sustained carbon storage program in Jammu and Kashmir where willows alone comprise a total population of around 37 million trees (departmental and private) with further scope for expansion as permanent marketable carbon sinks owing to the availability of about 15,082 km2 of waste land that could be used for plantation forestry.